Microbial utilization of recently fixed, plant-derived organic carbon in shallow Holocene and Pleistocene aquifers in Bangladesh. (March 2023) - Whaley-Martin, K.J.; San Pedro, R.J.; Mailloux, B.J.; Bostick, B.C.; Ahmed, K.M.; Mozumder, R.; Ellis, T.; van Geen, A.; Slater, G.F.
Highlights: Carbon cycles in Bangladesh aquifers significantly affect microbial As release. Sterol biomarkers and Δ 14 C of PLFA used to examine carbon source cycling. Δ 14 C of PLFA confirmed preferential utilization of young carbon sources regardless of sediment age. Both plant and sewage carbon sources are capable of stimulating arsenic release. Supply of young plant-derived organic carbon to shallow Pleistocene sediments has yet to result in As release. Abstract: The presence of dissolved arsenic in shallow aquifers of Bangladesh is widely accepted to require microbial dissimilatory iron-reduction in anoxic aquifers utilizing organic carbon as an electron donor. However, the various potential sources of this carbon, and whether organic carbon sources vary with sediment age (i.e. < 12 kyr-old Holocene vs older Pleistocene sediments) are still poorly understood. To shed light on these questions, natural abundance radiocarbon signatures of in situ microbial phospholipids fatty acids (PLFA), concentrations of sterol biomarkers, and aqueous [Cl - ] and [Br - ] were compared in two Bangladesh aquifers; a shallow (11–15 m) aquifer low in dissolved arsenic containing oxidized (orange) Pleistocene sands, Dopar Tek (DT), and a shallow (6–21 m) aquifer high in dissolved arsenic containing reduced (grey) Holocene sands, Desert Island (DI). Radiocarbon signatures of PLFA (Δ 14 CPLFA  = −30 to −63 ‰ and +9 to +25 ‰, respectively) indicate microbial utilization of carbon fixed from the atmosphere within the last several decades, the drawdown of which into the shallow portions of both the Pleistocene Dopar Tek and Holocene Desert Island aquifers was likely enhanced by regional pumping activities. Similar results were previously obtained for two other Holocene aquifers in the same region, but to our knowledge this is the first time modern PLFA has been extracted from Pleistocene sediments. At both sites, high proportions of phytosterols, low sewage contamination indices (SCI < 0.7), and generally low Cl/Br ratios (averaging 434 and 544 at Desert Island and Dopar Tek respectively), are consistent with predominantly plant-derived organic carbon inputs. This contrasts with sewage-derived input inferred from higher sewage contamination index values (>0.7) previously observed at the two other shallow Holocene aquifers in the same region. Overall, our observations show that microbial communities within shallow aquifers, including those of Pleistocene age, utilize very recently fixed organic carbon associated with both plant and/or sewage origin. The microbial utilization of organic carbon fixed within the past several decades, likely derived from plants, in the anaerobic Pleistocene, has not, as of yet, led to iron reduction that would be sufficient to increase arsenic concentrations in groundwater. However, the observed microbial utilization of recently fixed carbon within all Bangladesh aquifers studied to date, indicates that pumping enhanced drawdown represents a potential risk to any systems where it might occur.